The “Manguni” Wing in the Traditional Product Market Segment: The Case of Bamboo Craft MSMEs - Ani Putri; Jovelia Kojongian; Natasha Pontoh (Proceeding International Conference on Accounting and Finance, 2025)
This study examines the development strategy of bamboo craft MSMEs in Tomohon, North Sulawesi, by integrating the local philosophy of "Manguni" into business practices. This philosophy reflects wisdom, precision, and adaptability in facing challenges. This study utilizes the population of financial reports of bamboo craft MSMEs in 2019, 2020 and 2021. Return on Equity (ROE) analysis is needed in this study to measure the company's ability to gain profit with its own capital. This study uses Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and SWOT matrix analysis to evaluate internal and external factors that influence business sustainability. The results of the study indicate that the implementation of local wisdom-based strategies can increase the competitiveness of MSMEs, both in domestic and international markets, without eliminating their traditional values. This approach also emphasizes the importance of capital management and the implementation of management accounting in supporting product innovation and more effective marketing. This study recommends continued support from the government through training, incentives, and cultural promotion to strengthen the position of traditional MSMEs in the modern era.